SKILL DEVELOPMENT IN EXPERIMENTAL COURSES - Héctor Bagán (Journal of Technology and Science Education, 2015)
Experimental courses ofer a good opportunity to work with competences, promotng the incorporaton ofstrategies oriented towards motvatng students to actvely involve in the learning process, promotng refexivelearning and developing generic skills. This study presents diferent ways of developing and evaluatng someimportant general skills, setle on four specifc objectves: •to increase student motvaton using samples of potental interest to students and explaining real-liveapplicaton of their samples analyses;•to assist students’ self-regulaton and learning autonomy by using the portolio;•to promote group work through experiments in pairs and small-group discussions;•to develop communicaton skills through small-group discussions and oral presentatons. Results show that the type of sample used and real-life applicaton has important infuence on motvaton. Theportolio is a good tool to promote refecton and to evaluate both specifc and generic skills in experimentalcourses, the dynamics of a laboratory course permit students to develop their group-work and communicatveskills, and peer evaluatons both improve students’ communicaton skills and promote metacognitve refecton.Finally, the project demonstrates that it is possible to train students in general skills using the specifc coursecontent and that the incorporaton of partcipatory methodologies encourages students to become actvelyinvolved in the teaching-learning process.